Implementation of a Pilot Plant for the Integral Development of Remote Laboratories - Espinoza, Juan Valdiviezo; Alama, William Ipanaque; Bohorquez, Juan Soto; Amaya, Ivan Belupu (IEEE-RITA, 2021)
This article is an integral proposal of remote laboratories that complements the classes and the traditional laboratories of the subjects of Automation at Universidad de Piura. Four control loops have been implemented in the FESTO Compact Workstation pilot plant to remotely manipulate them: level control, flow control, pressure control and temperature control. In each one of them, the students must identify the open-loop process, understand the nature of the process and finally control it in a closed - loop, all this in an automated and remote way through the Internet. EasyPort and DirectLogic06 PLC have been used for module control, DirectSOFT software for PLC programming, FESTO Didactic EzOPC and NI OPC Servers for communication, and mainly LabVIEW for graphic interface and data processing.